2012
DOI: 10.2147/cia.s33893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of circuit-based exercise programs on the body composition of elderly obese women

Abstract: AimThe aim of this study was to investigate the impact of circuit-based exercise on the body composition in obese older women by focusing on physical exercise and body weight (BW) gain control in older people.MethodsSeventy older women (>60 years old) voluntarily took part in the study. Participants were randomized into six different groups according to body mass index (BMI): appropriate weight (AW) control (AWC) and trained (AWT) groups, overweight (OW) control (OWC) and trained (OWT) groups, and obesity (O) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 28 publications
3
74
0
5
Order By: Relevance
“…The number of repetitions ranged from 8 to 20, with a predominance of 8 to 12 repetitions (7 studies). In three studies 13,30,31 a time of 30 seconds to 1 minute was used to perform the repetitions. The percent load used, cited by 10 studies 12,15,20,22,23,25,[32][33][34]36 ranged from 40 to 75% 1 RM, and the load interval most frequently employed was 40 to 60% (6 studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of repetitions ranged from 8 to 20, with a predominance of 8 to 12 repetitions (7 studies). In three studies 13,30,31 a time of 30 seconds to 1 minute was used to perform the repetitions. The percent load used, cited by 10 studies 12,15,20,22,23,25,[32][33][34]36 ranged from 40 to 75% 1 RM, and the load interval most frequently employed was 40 to 60% (6 studies).…”
Section: Resultsmentioning
confidence: 99%
“…The percent load used, cited by 10 studies 12,15,20,22,23,25,[32][33][34]36 ranged from 40 to 75% 1 RM, and the load interval most frequently employed was 40 to 60% (6 studies). The interval between exercise series, cited by 6 studies 13,19,20,31,34,36 , ranged from 0 to 2 minutes, with no predominance of a specific interval (Table 2). Only one article 30 mentioned the speed of execution (5" to perform the movement) (result not shown in the table).…”
Section: Resultsmentioning
confidence: 99%
“…Participants were motivated in this longitudinal study, so the practice of PA was done on a daily basis 25. It has been found that persons with higher body weight have a lower motivation toward PA 26.…”
Section: Discussionmentioning
confidence: 99%
“…However, in previous studies, greater weight loss may occur in people with higher initial body mass 13,14 , which may be the case for MN women in relation to OS.…”
Section: Introductionmentioning
confidence: 84%